Analysis of Factors Influence Doctor's Decision in Choosing Patient's Referral to dr. Soepraoen Hospital Malang - Augustinus Budijono, Sebastian; Siyoto, Sandu; Noor Laila, Siti Farida (Master of Public Health Program Universitas STRADA Indonesia, 2019)
The importance of the role of health services causes the quality of health services to be improved because of the needs of the community or individuals for health. Second-level health services can only be given for referral from first-level health services. Third-level health services can only be given for referral from second- or first-level health services, except in emergency situations. Based on this, it can be seen that the first level Health Service Provider (PPK) has a very important role in the health care system in Indonesia. The purpose of this study was to find out the factors underlying the doctors to refer their patients to the dr. Soepraoen Army Hospital Malang. The research design used is quantitative research with a cross sectional approach. The sampling technique used was saturated sampling by taking 100 doctors as the study sample. The data analysis technique of this study uses linear regression by using an α value of 0.05. The results showed that hospital facilities had a significant effect on choosing a referral with a p-value of 0,000 with a t-count of 4,300, the availability of drugs had a significant effect on choosing a referral with a p-value of 0,000 with a t-count of 2,557 , the type of disease has a significant effect on choosing a referral with a p-value of 0,000 with a t-count value of 2,435, and on physician competence has a significant effect on choosing a referral with a p-value of 0,000 and a t-count value of 2,327, and simultaneously for each facility variable, drug availability, type of disease and physician competence can have a significant effect on choosing a referral. and found that the dominant factor influencing the decision to choose referral is the facility factor. The low analysis of factors that influence the doctor's decision in choosing a patient's referral to dr. Soepraoen Army Hospital Malang can be minimized by further increasing the indicator indicators of each variable that is considered still low.